1979
DOI: 10.1128/jvi.29.3.964-972.1979
|View full text |Cite
|
Sign up to set email alerts
|

Defective retrovirus-like 30S RNA species of rat and mouse cells are infectious if packaged by type C helper virus

Abstract: RNA species with properties of defective retrovirus-like 30S RNA genomes have previously been detected in both rats and mice and in some rat and mouse retroviruses. Using cell lines which express high levels ofthis retrovirus-like RNA, we formed pseudotypes of the 30S RNAs with helper-independent type C viruses. A pseudotype virus complex containing a mouse 30S subunit was transmitted to rat cells, and a pseudotype virus complex containing a rat 30S subunit was transmitted to bat cells. In other transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 26 publications
0
34
1
1
Order By: Relevance
“…The rat2 cell line was chosen as the parent for the construction of producer cell lines because they do not express endogenous proviruses closely related to MuLV. These cells, however, do express VL30 RNA, a retroviruslike RNA which is known to be pseudotyped by type C viruses (47). VL30 sequences appear to be either too defective or not similar enough to MuLV to generate replicationcompetent recombinants since no spontaneous revertants of point mutations were observed in rat2 cells.…”
Section: Most Of the Mutations That We Have Constructed In Thementioning
confidence: 99%
“…The rat2 cell line was chosen as the parent for the construction of producer cell lines because they do not express endogenous proviruses closely related to MuLV. These cells, however, do express VL30 RNA, a retroviruslike RNA which is known to be pseudotyped by type C viruses (47). VL30 sequences appear to be either too defective or not similar enough to MuLV to generate replicationcompetent recombinants since no spontaneous revertants of point mutations were observed in rat2 cells.…”
Section: Most Of the Mutations That We Have Constructed In Thementioning
confidence: 99%
“…In two of these studies, a third RNA component, slightly smaller than 32S, was reported and considered an additional genomic RNA of SFFV (36) or of an endogenous virus (15). It has not been shown that the presence of 32S RNA in SFFV(Fr-MLV) is necessary to induce spleen foci in mice, nor was it ruled out that the 32S RNA associated with SFFV(Fr-MLV) was a viral contaminant such as the 30S defective retrovirus-like RNAs present in some stocks of MLVs (17,26,44,45). To test directly whether the 32S RNA associated with SFFV(Fr-MLV) is correlated with spleen focus formation, we have examined the spleen focus-forming activity and the RNA components of viruses released from FRE cells and FRE cells nonproductively infected with SFFV before and after superinfection with Fr-MLV.…”
Section: Resultsmentioning
confidence: 99%
“…This could arise by deletion of a recombinant virus carrying Fr-MLV and amphotropic MLV sequences or by unequal crossing-over between two viruses with such sequences, resulting in specific deletions. Alternatively, SFFV could be the product of recombination between Fr-MLV and amphotropic MLV and an unknown defective prototype of SFFV possibly analogous to the 30S defective retrovirus-like RNA found in mouse and rat cells (17,26,44,45). This hypothesis would explain the defectiveness of SFFV because one of the parents of SFFV would itself be defective.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of VL30 retrotransposons is that they can be packaged into MLV virions, leading to their horizontal spread during retrovirus dissemination (17,19,33,34,67,78,79). Based on this observation, we asked whether the 5Ј region of VL30m RNA could replace the MLV Eϩ sequence functionally in a recombinant viral RNA.…”
Section: Discussionmentioning
confidence: 99%
“…VL30m elements do not encode virus-like proteins, have little sequence homology to Moloney murine leukemia virus (MoMLV) and have not been implicated in retroviral carcinogenesis (16,27). However, VL30 RNA possesses the unusual property of being packaged into MLV particles that are propagated in cell culture (17,19,33,34,67,78,79). As a consequence, VL30 elements are able to retrotranspose from cell to cell at high frequency via MLV particles (17,27).…”
mentioning
confidence: 99%